Optimization of tween 80 and PEG-400 concentration in Indonesian virgin coconut oil nanoemulsion as antibacterial against Staphylococcus aureus - Miksusanti; Apriani, Elsa Fitria; Bihurinin, Azzahra Hiththah Bama (Universiti Kebangsaan Malaysia, 2023)
Virgin Coconut Oil (VCO) can act as an antibacterial due to free fatty acids. To increase the stability of VCO, the VCO can be formed into nanoemulsion preparations. This study aimed to optimize the concentration of Tween 80 and Polyethylene glycol-400 (PEG-400) in nanoemulsion formula and determine antibacterial activity against Staphylococcus aureus. The content of VCO was determined using Gas Chromatography-Mass Spectrometry (GC-MS), and the results showed that VCO contained lauric acid, palmitic acid, caprylic acid, oleic acid, capric acid, and stearic acid. Optimization was carried out using the 22 factorial design method on the response of pH, density, percent transmittance, particle size, and polydispersity index. The optimum formula was obtained at concentrations of Tween 80 and PEG-400 40% and 26%, respectively, with a desirability value of 0.961. The optimum formula showed no phase separation and a significant decrease in pH (p>0.05). The optimum and comparison formula (pure VCO) had significantly different antibacterial activity (p<0.05) where the diameter of the inhibition zone was 24.77±1.66 mm and 16.73±2.00 mm, Minimum Inhibitory Concentration (MIC) of 1250 ppm and 2500 ppm, Minimum Bactericidal Concentration (MBC) of 2500 ppm and more than 2500 ppm, respectively. The optimum formula of VCO nanoemulsion was proven to have good stability and a potent antibacterial activity.